Electromagnetic band gap structures in antenna engineering - Yang, Fan 1975- (The Cambridge RF and microwave engineering series, 2008)
This comprehensive, applications-oriented survey of Electromagnetic Band Gap (EBG) engineering explains the theory, analysis, and design of EBG structures. It helps you to understand EBG applications in antenna engineering through an abundance of novel antenna concepts, a wealth of practical examples, and complete design details. You discover a customized FDTD method of EBG analysis, for which accurate and efficient electromagnetic software is supplied (www.cambridge.org/9780521889919) to provide you with a powerful computational engine for your EBG designs. The first book covering EBG structures and their antenna applications, this provides a dynamic resource for engineers, and researchers and graduate students working in antennas, electromagnetics and microwaves.